2018
DOI: 10.1155/2018/6142065
|View full text |Cite
|
Sign up to set email alerts
|

Curative Anti‐Inflammatory Properties of Chinese Optimized Yinxieling Formula in Models of Parkinson’s Disease

Abstract: Parkinson's disease (PD) is marked by the progressive degeneration of dopaminergic neurons (DAN) accompanied by glial activation. Thus, inhibiting glial activation that occurs during this disease could be an effective method for treating PD. Optimized Yinxieling Formula (OYF), a Chinese medicinal formula, which is used to efficiently treat autoimmune disease psoriasis, has been proved to display potential immunomodulatory effects in inflammation-associated diseases. This study assessed the therapeutic benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Evidence-Based Complementary and Alternative Medicine Furthermore, in the in vitro experiment, IFN-c stimulation upregulated TNF-α, IL-1β, and IL-6 mRNA levels in RAW264.7 cells, whereas a high dose of OYFCS reversed the elevated levels ( Figure 5). ese results were similar to our previous study in the MPTP-induced mice model and in LPSinduced BV-2 cells [15]. Taken together, these results suggest that OYF exerts an antiinflammation effect in the PD model.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Evidence-Based Complementary and Alternative Medicine Furthermore, in the in vitro experiment, IFN-c stimulation upregulated TNF-α, IL-1β, and IL-6 mRNA levels in RAW264.7 cells, whereas a high dose of OYFCS reversed the elevated levels ( Figure 5). ese results were similar to our previous study in the MPTP-induced mice model and in LPSinduced BV-2 cells [15]. Taken together, these results suggest that OYF exerts an antiinflammation effect in the PD model.…”
supporting
confidence: 91%
“…Other population-based cohort studies also showed that psoriasis patients had significantly higher risk of developing PD, suggesting a potential relation between PD and psoriasis [28]. Given that inflammation is the common pathology of PD and psoriasis and that the OYF had antiinflammation property in treating psoriasis, our previous study investigated the effects of OYF in the MPTP-induced PD mouse model and found that OYF attenuated the loss of dopaminergic neurons in SN and alleviated the inflammatory response [15]. In addition to the MPTP-induced model, there are other commonly used animal models of PD that employ toxins, including 6-OHDA, which is similar to DA in structure and can specifically kill dopaminergic neurons and their terminals [16].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, its preventive and therapeutic effects have been observed, among others, in psoriasis and NDs, including PD, AD, and ALS. Wei et al assessed the efficacy of the optimized yinxieling formula (OYF), which is a Chinese medicinal formula successfully used in psoriasis therapy, in PD (Wei et al, 2018 ). They found beneficial OYF influence on the suppression of inflammation and immunomodulatory properties and suggested it could be useful also in PD (Wei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the excessive activation of proinflammatory phenotypes caused by microglia can lead to chronic inflammation and consequently accelerate oxidative stress and apoptosis induced death oftheneurons. An in vivo study showed that optimized Yinxieling formula inhibited the activation of microglia and suppressed the secretion of proinflammatory cytokines in the MPTP-induced PD mouse models via down-regulation of the NF-κB signaling pathway, which protected the DA neurons from immune-mediated death [21]. Similar effects were found in an Aβ1-42-induced AD mouse model treated with an A. oxyphylla-Schisandra chinensis herbal formulation and an LPS-induced AD mouse model treated with Nootkatone derived from A. oxyphylla [29,31].…”
Section: Regulation Of Immunomodulation and Neuroinflammationmentioning
confidence: 99%